2006
DOI: 10.1063/1.2378561
|View full text |Cite
|
Sign up to set email alerts
|

Prompt gamma measurements for locating the dose falloff region in the proton therapy

Abstract: The location of the distal falloff in the proton therapy is an important but often uncertain parameter as different tissue elements are traversed by the beam. A multilayered collimator system has been constructed as a practical means to locate the dose ends by measuring prompt gammas. The collimator is designed to moderate and capture fast neutrons and to prevent unwanted gammas from reaching the scintillation detector. The system has been studied using Monte Carlo technique and has been tested in the beam ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
313
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 385 publications
(320 citation statements)
references
References 12 publications
6
313
0
1
Order By: Relevance
“…2 shows the experimental setup to measure the distribution of the prompt gammas at the National Cancer Center (NCC, Korea). The prompt gamma scanning system developed in a previous study 4,5) was used to scan the distribution of the prompt gammas in a water phantom (20 cm x 20 cm x 30 cm), while a 150 MeV pencil-type proton beam was delivered to the center of the phantom. The beam current was roughly 2 nA, and each scanning point was measured for 10 sec.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 shows the experimental setup to measure the distribution of the prompt gammas at the National Cancer Center (NCC, Korea). The prompt gamma scanning system developed in a previous study 4,5) was used to scan the distribution of the prompt gammas in a water phantom (20 cm x 20 cm x 30 cm), while a 150 MeV pencil-type proton beam was delivered to the center of the phantom. The beam current was roughly 2 nA, and each scanning point was measured for 10 sec.…”
Section: Methodsmentioning
confidence: 99%
“…4,5) The scanning system measures only the rightangled or 90° prompt gammas to determine the distribution of the 'origins' of the prompt gammas along the beam passage in the patient. It was found, however, that a significant amount of high energy spallation neutrons are also generated from the protons in the medium, and that the resulting background gammas significantly affect the measurement.…”
Section: Introduction *mentioning
confidence: 99%
“…Initial studies have found a good correlation between dose delivery and prompt-gamma emission, 9,10 and small shifts in the Bragg peak position can be detected by measuring prompt-gamma emission during treatment. 11,12 Recent studies have also shown that the intensities of the characteristic prompt-gamma spectral lines from individual elements are directly proportional to the concentration of the elements in tissue, 13 so prompt-gamma imaging could provide a path to spectroscopic analysis of irradiated tumors and healthy tissues.…”
Section: In Vivo Imagingmentioning
confidence: 99%
“…The emitted positrons annihilate with electrons of the tissue to produce pairs of coincident 511 keV gamma photons [3]- [4]. Another is called prompt gamma (PG) imaging [5]- [7], which relies on the measurement of single gamma photons promptly emitted from some excited tissue nuclei following their decays from the excited states to their ground states. The PET-based range verification technique has been adopted for the post-treatment quality control [8], but it still has some limitations.…”
Section: Introductionmentioning
confidence: 99%